The Effect of Concurrent Use of Lower Extremity and Spinal Orthotics Intervention to Improve Activity Daily Living and Quality Of Life in Charcot-Marie-Tooth Disease: A Single-Subject Design - Jiryaei, Zahra; Jiryaei, Alireza (Journal of Clinical Physiotherapy Research, 2019)
Introduction: The Charcot-Marie-Tooth (CMT) disease causes the significant muscular deficits in the affected patients, inhibits activities daily living, and involves a severe disability. The aim of this study was to evaluate the effect of concurrent use of a knee-ankle foot orthosis along with a body jacket orthosis to improve activities daily living in a person with CMT. Methods and Materials: A boy aged 16 years old with CMT was evaluated in this case report. He had a sever Kypho-scoliosis deformity in his spine and sever equines in his feet with unstable knee. In order to control of knees and ankles simultaneously, an ankle foot orthosis with the supracondylar trimline was designed. The control of his sever spinal deformity was also provided by a body jacket over shoulder. To evaluation of activities daily living, subject was asked to filled Barthel index out during a week. After one month, the individual was asked to fill the Barthel index out again. Finally, user friendly of orthotics were evaluated by a satisfaction questionnaire. Results: The results indicated that the orthoses was capable to improve activity daily living (25 percent increase after using orthosis in Barthel index). Also, results showed 30 percent increase after using orthosis for the QOL questionnaire. The mean of scale in satisfaction questionnaire were 4.5 based on Likert scale. Conclusion: This single-case study demonstrated the control of spinal and lower limb is simultaneously necessary for the improvement of activity daily living. Key words: ADL, QOF, Charcot-Marie-Tooth, Orthotics And Spinal Deformity